The Flooding Effect from Rice Cultivation Technique on Infiltration and Water Balance - Supriatin, Lilik Slamet; Basukriadi, Adi; Thayeb, M. Hasroel; Soesilo, Tri Edi Budi (Forum Geografi, 2013)
Flood events are often inundated rice fields and can cause flooding to surrounding areas (the lower reaches of the river) should not be underestimated (just blame the rainfall factor alone), but should be seen also internal factors of the techniques of rice cultivation in paddy fields. The purpose of research/study was to analyze the effect of flooding on the cultivation of paddy rice to infiltration and provide alternative solutions cultivation techniques to reduce flooding. The research method in this study is a survey method with the quantitative approach. Techniques flooding in paddy rice cultivation, especially irrigated cropping pattern rice 3 times a year have resulted in the formation of plow layer tread that is waterproof (hardpan). Waterproof coating that forms on the floor of paddy (rice surface) cannot infiltrate rainwater so that if there is a high-intensity rainfall in the rainy season, rice cannot hold the rain water will overflow and cause flooding to the area around the rice fields. Techniques inundation in lowland rice cultivation resulted in flooded paddy rice growth period in a rather long time (over 2 months), so that the aggregate soil is loose and prone to erosion and landslide potential. Anticipation of floods caused by wetland can be done by making the high rice fields higher than the height of the floodwaters that ever happened to the rice field and lowering the height of standing water in the paddy fields.